Pengaruh Kombinasi Mikro Organisme Lokal Bonggol Pisang Dan Pupuk NPK Terhadap Pertumbuhan Tanaman Jagung Manis (Zea mays saccharata strurt L.) Varietas Bonanza - Darso Sugiono; Dian Andiyani (Jurnal Ilmiah Wahana Pendidikan, 2023)
One of the limiting factors for sweet corn plant growth is nutrients. The state of nutrients in the soil will determine the yield of sweet corn. To achieve optimum results sweet corn plants require adequate nutrient input. Nutrients are one of the important factors that affect plant growth and development. Fertilization as nutrient fulfillment can be done through the application of a combination of micro organism local (Mol) fertilizer banana hump and NPK compound fertilizer. Provision of micro organisms local and NPK compound fertilizers on sweet corn plants is useful for accelerating the destruction of organic matter, can also serve as additional nutrients and nutrients needed by plants, so as to increase growth and yield of sweet corn plants as expected. The research method used is an experimental method using a single factor randomized block design (RBD). The number of treatments used in this study were 10 treatments which were repeated 3 times. So there are 30 experimental units. The treatments were as follows: A. 300 kg/ha NPK, B. 10 l/ha Mol + 300 kg/ha NPK, C. 20 l/ha Mol + 300 kg/ha NPK, D. 30 l/ha Mol + 300 kg/ha NPK, E. 10 l/ha Mol + 250 kg/ha NPK, F. 20 l/ha Mol + 250 kg/ha NPK, G. 30 l/ha Mol + 250 kg/ha NPK, H. 10 l/ha Mol + 200 kg/ha NPK, I. 20 l/ha Mol + 200 kg/ha NPK, J. 30 l/ha Mol + 200 kg/ha NPK, K. No fertilizer (control). The results showed that the combination of micro organisms local of banana weevil and NPK fertilizer had a significant effect on the growth components. Treatment G with 30 l/ha MOL + 250 kg/ha NPK gave the highest yield of growth components.